(untitled) - Macome, Felicidade Margarida (Netherlands, 2017)
The aim of this thesis was to determine the relationship (if any) between in vivo CH4 production obtained using climate controlled respiration chambers and in vitro CH4 production using the gas production technique. The in vitro techniques are routinely used to evaluate the nutritional quality of feeds and feed ingredients as they have an advantage of being less expensive, less laborious and allow maintenance of more precise experimental conditions than in vivo studies. It is well known that gas in the gas production (GP) technique is produced after the fermentation of the substrate where CO2 and methane (CH4) are produced as direct gas, and indirect gas is produced from the buffering of short chain fatty acids (SCFA). Studies investigating the relationship between in vitro and in vivo CH4 production by cows fed the same feed as substrate used in in vitro incubations are rare in the literature. It is important to have an accurate prediction on CH4 production of rations to be fed in practice.
Keywords: Gia súc,Cattle; Thức ăn và cho ăn,Feeding and feeds